2020
DOI: 10.1016/j.ijid.2020.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the predictive factors for a critical illness of COVID-19 during treatment - relationship between serum zinc level and critical illness of COVID-19 −

Abstract: Highlights Close relationship is found between low serum zinc and severe states of COVID-19. Hypozincemia critically contributes to aggravation of COVID-19. Serum zinc level can be predictive factor for critical illness of COVID-19. We would recommend oral medication of zinc salts to patients with COVID-19. Abstract Objectives Because most severely ill patients with COVID-19 in our h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(99 citation statements)
references
References 26 publications
4
93
0
2
Order By: Relevance
“…5,6,16 Recently, Yasui et al reported that decreased levels of zinc, an activator of immune cells that regulate cell-mediated immunity, could be related to Covid-19 severity. 19 Moreover, Tan et al reported elevated CRP levels and ESR at a very early stage of Covid-19. 6 They suggested that elevated CRP levels and ESR could predict the occurrence of severe disease before CT findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6,16 Recently, Yasui et al reported that decreased levels of zinc, an activator of immune cells that regulate cell-mediated immunity, could be related to Covid-19 severity. 19 Moreover, Tan et al reported elevated CRP levels and ESR at a very early stage of Covid-19. 6 They suggested that elevated CRP levels and ESR could predict the occurrence of severe disease before CT findings.…”
Section: Discussionmentioning
confidence: 99%
“…reported that decreased levels of zinc, an activator of immune cells that regulate cell-mediated immunity, could be related to Covid-19 severity. 19 Moreover, Tan et al . reported elevated CRP levels and ESR at a very early stage of Covid-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another uncontrolled case series study with COVID-19 patients, a high dose of oral zinc salt resulted in clinical recovery, improved oxygenation, and less shortness of breath among those patients [95] . A study conducted in Japan on 62 patients with COVID-19 showed a close association between low serum zinc level and severity of the disease [5] . The investigators also found serum zinc level as a predictive factor for a critical illness of patients with COVID-19 [5] .…”
Section: Zinc: Effects On Covid-19 Patientsmentioning
confidence: 98%
“…Zinc deficiency is associated with a higher rate of infections, degenerative diseases, oral diseases, and behavioral disorders in humans [1] , [4] . Available information suggests that zinc deficiency is associated with increased disease severity of the COVID-19 [5] . In a comprehensive metal(loid)s analysis, compared to the non‐severe COVID‐19 patients, the whole blood chromium, calcium, and copper levels were higher, while the levels of zinc, magnesium, manganese, iron, lead, arsenic, and thallium were lower in the severe patients with COVID-19 [6] .…”
Section: Zinc: An Essential Trace Elementmentioning
confidence: 99%